2011
DOI: 10.1007/s12192-010-0231-9
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor activity of efrapeptins, alone or in combination with 2-deoxyglucose, in breast cancer in vitro and in vivo

Abstract: Efrapeptins (EF), a family of fungal peptides, inhibit proteasomal enzymatic activities and the in vitro and in vivo growth of HT-29 cells. They are also known inhibitors of F 1 F 0 -ATPase, a mitochondrial enzyme that functions as an Hsp90 co-chaperone. We have previously shown that treatment of cancer cells with EF results in disruption of the Hsp90:F 1 F 0 -ATPase complex and inhibition of Hsp90 chaperone activity. The present study examines the effect of EF on breast cancer growth in vitro and in vivo. As … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 30 publications
0
13
0
Order By: Relevance
“…Interestingly, Aft et al found that 2DG treatment of breast cancer cells resulted in the up-regulation of GLUT-1 and the accelerated uptake of glucose and 2DG. This indiscriminate uptake is detrimental to the cells [86].…”
Section: The Potential For 2dg Usementioning
confidence: 99%
“…Interestingly, Aft et al found that 2DG treatment of breast cancer cells resulted in the up-regulation of GLUT-1 and the accelerated uptake of glucose and 2DG. This indiscriminate uptake is detrimental to the cells [86].…”
Section: The Potential For 2dg Usementioning
confidence: 99%
“…The analogs of efrapeptins contain alpha-azide carboxylic acid ( Figure 4, Table 2). Efrapeptins have antifungal, antimalarial, insecticidal and antitumor activities [20,23]. In particular, they can inhibit the ATPase and, disturb the interaction between ATPase and heat shock protein 90 (Hsp90) [24][25][26].…”
Section: Efrapeptinsmentioning
confidence: 99%
“…F 1 F 0 ATP synthase was proposed to possess co-chaperone function by interacting with Hsp90 in several different cancer cell lines [28,43]. Furthermore, inhibition of F 1 F 0 ATP synthase directly affected client protein maturation.…”
Section: Introductionmentioning
confidence: 99%
“…Hsp90 requires ATP for chaperone activity and inhibition of ATP synthase with pan ATP synthase inhibitors such as oligomycin A, 2-deoxy-D-glucose, antimycin A and efrapeptins prevent Hsp90-dependent client maturation, which destabilizes the client–Hsp90 complex, leading to client degradation via the proteosome (Figure 3) [43,48,49]. ATP synthase inhibitors do not induce the HSR, as oligomycin A and efrapeptins manifested little to no increase in Hsp90, Hsp70 and Hsp27 levels.…”
Section: Introductionmentioning
confidence: 99%